Translation in the mammalian oocyte in space and time - Susor, Andrej; Jansova, Denisa; Anger, Martin; Kubelka, Michal (Cell and tissue research, 2016)
A hallmark of oocyte development in mammals is the dependence on the translation and utilization of stored RNA and proteins rather than the de novo transcription of genes in order to sustain meiotic progression and early embryo development. In the absence of transcription, the completion of meiosis and early embryo development in mammals relies significantly on maternally synthesized RNAs. Post-transcriptional control of gene expression at the translational level has emerged as an important cellular function in normal development. Therefore, the regulation of gene expression in oocytes is controlled almost exclusively at the level of mRNA and protein stabilization and protein synthesis. This current review is focused on the recently emerged findings on RNA distribution related to the temporal and spatial translational control of the meiotic progression of the mammalian oocyte.
Keywords: transkriptom; oocyty; vývojová regulace genové exprese; Gene Expression Regulation, Developmental; Protein Biosynthesis; proteosyntéza; Transcriptome; Meiosis; meióza; oogeneze; Animals; Translation; lidé; RNA; Humans; zvířata; RNP; Oocyte; Oogenesis; Oocytes